Fine‐scale population structure and connectivity of bottlenose dolphins, Tursiops truncatus, in European waters and implications for conservation. (6th September 2019) - Nykänen, Milaja; Louis, Marie; Dillane, Eileen; Alfonsi, Eric; Berrow, Simon; O'Brien, Joanne; Brownlow, Andrew; Covelo, Pablo; Dabin, Willy; Deaville, Rob; de Stephanis, Renaud; Gally, François; et al.
Abstract: Protecting species often involves the designation of protected areas, wherein suitable management strategies are applied either at the taxon or ecosystem level. Special Areas of Conservation (SACs) have been created in European waters under the Habitats Directive to protect bottlenose dolphins, Tursiops truncatus, which forms two ecotypes, pelagic and coastal. The SACs have been designated in coastal waters based on photo‐identification studies that have indicated that bottlenose dolphins have relatively high site fidelity. However, individuals can carry out long‐distance movements, which suggests potential for demographic connectivity between the SACs as well as with other areas. Connectivity can be studied using genetic markers. Previous studies on the species in this area used different sets of genetic markers and therefore inference on the fine‐scale population structure and demographic connectivity has not yet been made at a large scale. A common set of microsatellite markers was used in this study to provide the first comprehensive estimate of genetic structure of bottlenose dolphins in European Atlantic waters. As in previous studies, a high level of genetic differentiation was found between coastal and pelagic populations. Genetic structure was defined at an unprecedented fine‐scale level for coastal dolphins, leading to identification of five distinct coastal populations inhabiting the following areas: Shannon estuary, west coast of Ireland, English Channel, coastal Galicia, east coast of Scotland and Wales/west Scotland. Demographic connectivity was very low among most populations with <10% migration rate, suggesting no demographic coupling among them. Each local population should therefore be monitored separately. The results of this study have the potential to be used to identify management units for bottlenose dolphins in this region and thus offer a significant contribution to the conservation of the species in European Atlantic waters. Future studies should prioritize obtaining biopsies from free‐living dolphins from areas where only samples from stranded animals were available, i.e. Wales, west Scotland and Galicia, in order to reduce uncertainty caused by sample origin doubt, as well as from areas not included in this study (e.g. Iroise Sea, France). Furthermore, future management strategies should include monitoring local population dynamics and could also consider other options, such as population viability analysis or the incorporation of genetic data with ecological data (e.g. stable isotope analysis) in the designation of management units.